Perancangan Dan Pembuatan Generator Fluks Radial Tiga Fasa Magnet Permanen Kecepatan Rendah - Andika, Andika; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Based on wind speed data from Meteorology and Geophysics Agency, Indonesia has an average wind speed of about 3-6 m / s. Wind speed can be categorized at low wind speed. So the power station needs a low-speed generator. One solution found from this problem is the development of low speed power plant technology. The wind power plant has an important component of which is a generator which is an electric machine that convert mechanical energy into electrical power. By utilizing a low speed and high torque of the direct drive system of the wind turbine. In designing this low-speed generator the magnetic field is made of neodynium magnets. The generator is designed with a speed of 750 rpm, frequency 50 Hz, induced voltage 15 V and 3 phase. Permanent magnet used with a diameter of 20mm and 3mm thick. The tests included zero load testing, load testing, anchor resistance testing, short-circuit testing and calculating voltage regulation. At the load-bearing load and weightless testing there is a decrease in stress due to the load, where the voltage regulation at the R phase is 16.1%, the S phase is 16.8% and the T phase is 13.2%. The yielded generator voltage phase S is 10.1 Vac, voltage phase R is 10.2 Vac, and then voltage phase T is 10.3 Vac.Keywords: Radial flux generator, neodynium magnet, design result